Nest Characteristics of the Introduced Orangutan at Jantho Orangutan Reintroduction Station, Aceh Besar - Irmayuni; Onrizal; Suwarno (Journal of Sylva Indonesiana, 2023)
Sumatran orangutans (Pongo abelii) learned the process of building nests from their mothers and started building nests around the age of 0.5 years. Orangutan nests have the most intricate arrangement of other primate nests. Orangutans built the nest as a place to rest, play, and protect themselves from predators and insect bites such as mosquitoes. Orangutan nests have different locations tailored to the needs and context of the nest trees. The shape of the nest and the position of the nest usually have differences due to differences in sex, age level, and body weight. The research had conducted at the Jantho Orangutan Reintroduction (JOR) Station, Aceh Besar Regency, Aceh Province. It had carried out from January to August 2021. The research method used is purposive sampling. The selected transects are existing (permanent) with FB, RI, and IS coding, which is part of mammalian transects scattered in the Jantho Pine Forest Nature Reserve. Observations were carried out as many as two repetitions in different months. The results showed several classes and nest positions found at the JOR Station. The nest classes found were 1, 2, and 3, while the others were not found. Nests in position 2 were the most founded at the study site, and position 5 was not found. It indicates no orangutan at the study site liked to play on the ground. This study gets four nest shapes, namely single round, flat oval, tiered, and irregularly widened